Integrating Spiritual and Moral Development Through the Tahfidz Program: A Holistic Educational Model - Bail Miya Turrohma; Benny Prasetiya; Anirut Nuplord (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to examine the implementation of the tahfidz program at Al Amri Islamic Boarding School, Probolinggo, as a holistic educational model that integrates spiritual formation, moral cultivation, emotional resilience, and disciplined memorization practices. The research addresses the gap in existing studies that often treat Quran memorization as a cognitive activity without systematically analyzing its multidimensional character-building functions. Employing a qualitative field research design, data were collected through participatory observations, in-depth semi-structured interviews with students, teachers, and administrators, and institutional document analysis. The data were analyzed using reflexive thematic analysis supported by methodological and source triangulation. The findings reveal that structured daily routines, meaning-based memorization, intensive mentoring (riāyah ṭ-ṭullāb), and quality-oriented evaluation significantly enhance memorization stability, emotional regulation, moral awareness, and spiritual depth. Discipline and responsibility gradually shift from external enforcement to internal self-regulation, strengthened by peer mentoring and communal culture. However, academic workload, mental fatigue, and fluctuating motivation remain challenges affecting memorization consistency. The novelty of this study lies in conceptualizing tahfidz as a holistic pedagogical framework that integrates cognitive mastery with spiritual–moral transformation and psychosocial support. This study contributes theoretically by expanding Islamic educational discourse on holistic character formation and practically by offering a structured model for designing sustainable, spiritually grounded tahfidz programs.